Skew-Circulant-Matrix-Based Harmonic-Canceling Synthesizer for BIST Applications - Guillermo G. Garayar-Leyva; Hatem Osman; Johan J. Estrada-López; Oscar Moreira-Tamayo (Sensors, 2022)
Testing is an important part of the design flow in the semiconductor industry. Unfortunately, it also consumes up to half of the production cost. On-silicon stimulus generators and response analyzers can be integrated with the Device-Under-Test (DUT) to reduce production costs with a minimum increment in power and area consumption. This practice is known as the Built-In Self-Test (BIST). This work presents a single-tone generator for BIST applications that is based on the Harmonic-Canceling (HC) technique. The main idea is to cancel or filter out the harmonics of a square-wave signal in order to obtain a highly pure sine wave. The design challenges of this technique are the precise implementation of irrational coefficients in silicon and the strong dependence of the output’s linearity on the coefficients’ precision. In order to reduce this dependence, this work introduces an irrational coefficient generator that is based on the recursive use of special matrices called skew-circulant matrices (SCMs). A complete study of the SCM-based HC synthesizer, its properties, and the proposed implementation in 180 nm CMOS technology are presented. The measured results show that the proposed HC synthesizer is able to filter out up to the 47th harmonic of a given square wave and to generate signals from <semantics>0.8</semantics> to 100 MHz with a maximum Spurious-Free Dynamic Range (SFDR) of 66 dB.